“Valiente”: Escritura narrativa para un cortometraje sobre la normalización de la violencia de género - Adrianzen Martinez, Valeria Sue (2022)
With this audiovisual project we intend to make a short film that shows the machismo that has been normalized in society and that goes unnoticed. For its development, we began with an exhaustive investigation on the subject since, in this way, we can better capture reality. The story was made considering what we want to show and transmit. We start with the storyline to get the general idea of the story, we continue with the synopsis and the script. Once this was finished, we proceeded to make a technical script accompanied by a photo board that serves as a reference at the time of recording. In parallel, the art area was worked on, where the moodboard, the locations, the costumes and the necessary props for the making of the short film were placed in a folder. Subsequently, a work plan was broken down by weeks to check all the activities to be carried out. Along with that, the project budget was prepared to be able to carry out the casting with the actors in mind, have the locations and all the props ready, and then proceed with the filming. After the days of filming, we went on to editing following the requirements set out at the beginning. Finally, having the short film ready, it begins with its dissemination at festivals and on social networks.